PERANCANGAN SISTEM INFORMASI KEPEGAWAIAN BERBASIS WEB SMP NEGERI 2 SEI BINGAI - Ocha Adela Br Siahaan; Yuniar Andi Astuti (Cemara Education and Science, 2025)
A personnel information system is a crucial requirement for managing employee data in educational institutions, such as SMP Negeri 2 Sei Bingai. Manually managing employee data leads to various problems, including recording errors, data duplication, and difficulty in finding information. Therefore, this research aims to design and develop a web-based personnel information system that can facilitate the management of employee data effectively and efficiently. The research methods used in designing this system include needs analysis and system design using the PHP programming language and MySQL database. The test results show that this system is able to improve accuracy and speed in managing staffing data, as well as facilitate access to information for schools.